Pursuing the mission of third sector organizations in the context of interorganizational networks: implications to strategy - Simaens, A. (EURAM 2019, 2019)
Third Sector Organizations (TSOs) face multiple sources of complexity in the pursuit of their missions, including institutional, problem, strategic, and operational complexities. This has demanded new forms of cooperation and interorganizational coordination. In the context of multiple networks of relationships, this paper explores a systems approach to mission pursuit. Based on an empirical study with twenty-three TSOs belonging to an interorganizational network, we explore not only the environmental interconnectedness and complexity they face, but also the role of interorganizational relationships within the boundaries of the network for mission pursuit. The findings suggest that these TSOs face multiple enablers and barriers in the pursuit of their missions, related to a set of interorganizational relationships. The mechanisms of competition and cooperation detected are also explored.